Adsorption of U(VI) from aqueous solution by Triocthylamine (TOA) functionalized magnetite nanoparticles as a novel adsorbent (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Adsorption of U (VI) from aqueous solutions was investigated using magnetically assisted chemical separation (MACS) process. In the present study, Triocthylamine (TOA) functionalized magnetite nanoparticles (TOAFMNPs) were applied as a novel adsorbent for adsorption of U (VI) from aqueous solutions. The effects of initial pH, Triocthylamine to magnetite nanoparticles weight ratio, amount of adsorbent, stirring time and initial U(VI) concentration on U(VI) adsorption efficiency were investigated by batch experiments. The adsorption of U(VI) using this adsorbent was pH dependent, and the optimal pH was 5.5. In kinetics studies, the adsorption equilibrium can be reach within 20 min., and the experimental data were well fitted by the pseudo-second-order model. The highest value of U(VI) adsorption (93.8%) was achieved in optimum conditions. The Langmuir isotherm model correlates well with the U(VI) adsorption equilibrium data for the concentration range 10-80 mg/l. The maximum U(VI) adsorption capacity onto adsorbent was 27.5 mg/g at room temperature. Present study suggests that TOAFMNPs could be employed as a potential adsorbent for U(VI) adsorption, and also could provide a simple and fast separation method for removal of U(VI) ion from solutions